Constitutional and legal framework of administrative justice in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The author considers the questions of constitutional and legal foundations of administrative justice. In particular, the authors reveal the concept, power and features of administrative justice in the Republic of Kazakhstan.Key words: administrative responsibility, administrative justice, administrative and tort law, the court participants.